Fourier coefficientes computation in two variables, a distributional version - Ulate R., Carlos Manuel (2015)
The present article, by considering the distributional summations of Euler-Maclaurin and a suitable choice of the distribution, results in repre- sentations for the Fourier coefficients in two variables are obtained. These representations may be used for the numerical evaluation of coefficients.